Student Creativity at Risk: A Scoping Review of the Negative Effects of Generative AI in University Education - Umán Juarez, Steve Jason; Hurtado Laura De Mera, Carmen Rosa; Alcántara Cuba De Byrne, Giovanna Irayda; Byrne Jaramillo, Luis Alberto; Chung Sanchez, Kenji Alberto (LACCEI, 2025)
Despite the growing use of generative artificial intelligence (AI) in higher education, there remains a limited critical understanding of its effects on key formative dimensions such as creativity. While its benefits are widely acknowledged, the associated risks have been insufficiently explored. In response to this gap, the present study conducted a scoping review aimed at identifying and analyzing the main negative effects of exposure to AI-generated content on student creativity. The methodological approach followed Arksey and O’Malley’s framework, complemented by the PRISMA 2020 diagram. The search was carried out in the Scopus database, restricted to open-access documents in English and Spanish, published between 2022 and 2025. From an initial set of 1,234 records, 26 studies met the inclusion criteria for full analysis. The findings were categorized into six emerging dimensions: cognitive, emotional, ethical, pedagogical, social, and technical. Common patterns included loss of divergent thinking, reduced originality, creative dependency, demotivation, and the deterioration of critical judgment. It is concluded that the negative impact of AI on creativity is neither uniform nor inevitable, but rather conditioned by the pedagogical, ethical, and formative frameworks guiding its use.